Menjadi Pribadi yang dapat Dipercaya - Christofora Megawati Tirtawinata (Bina Nusantara University, 2013)
Any relationship of any nature with whoever we relate to each other is needed trustworthiness or credible. The reality in the life of many cases that resulted in a loss of trust caused by the individual can not be trusted. Everyone wants to be a person who can be trusted, but not everyone can become a person who can be trusted, even more rare because it can be said that the most serious challenge to become a person that can be trusted is against yourself, because the necessary humility and courage release selfishness, and fight for the truth. This article draws empirical studies and literature, which explains about the elements needed to become a person that can be trusted. Elements of credibility related to the integrity of the character: integrity and intent, while related to the competence: capability and result, and how to improve the quality of these elements, so that eventually you can become a person who can be trusted.